Effect of W-Mo doping on the phase transition temperature of VO2 synthesized by hydrothermal microwave method - Yan Liu; Tienan Jiang; Yang Lv; Xinyu Zhou; Henan Zhu; Qihui Shen (Materials Research Express, 2023)
In this study, the combination of hydrothermal microwave technology and high-temperature method was used to efficiently control the formation of M-phase vanadium dioxide (VO _2 ) nanoparticles, which were promising materials for optoelectronic switches and smart windows due to their excellent optoelectronic properties during the phase transition. The phase state and structure of VO _2 depended on its synthesis parameters, and the results showed that the optimal conditions for VO _2 (B) synthesis in a hydrothermal microwave were 120 °C for 2 h, which was a novel method for efficiently preparing VO _2 (B) at a low temperature. By vacuum annealing, VO _2 (B) could be transformed into monoclinic VO _2 (R), where VO _2 (R) converts into VO _2 (M) on cooling to room temperature. Furthermore, the phase transition temperature of W-Mo co-doped VO _2 (M) decreased by 14.8 °C, showing that the incorporation of W-Mo elements into the VO _2 -based structure affects the material’s phase transition temperature.